2021
DOI: 10.1136/bmjopen-2020-046207
|View full text |Cite
|
Sign up to set email alerts
|

Do people living in rural and urban locations experience differences in harm when admitted to hospital? A cross-sectional New Zealand general practice records review study

Abstract: ObjectiveLittle is known about differences in hospital harm (injury, suffering, disability, disease or death arising from hospital care) when people from rural and urban locations require hospital care. This study aimed to assess whether hospital harm risk differed by patients’ rural or urban location using general practice data.DesignSecondary analysis of a 3-year retrospective cross-sectional general practice records review study, designed with equal numbers of rural and urban patients and patients from smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…In this dataset, adverse event deaths were least likely in the most urban category, and more common in the two remaining (more rural) categories. As such, the findings were generally in contrast to previous reports ( Atmore et al, 2021 , Coburn et al, 2004 , Vartak et al, 2010 ) but in line with the present hypothesis. With regard to previous reports, the differing geographical coverages, time periods, definitions of urbanity and rurality, and adverse event outcomes should be acknowledged as potential sources of discrepancy.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In this dataset, adverse event deaths were least likely in the most urban category, and more common in the two remaining (more rural) categories. As such, the findings were generally in contrast to previous reports ( Atmore et al, 2021 , Coburn et al, 2004 , Vartak et al, 2010 ) but in line with the present hypothesis. With regard to previous reports, the differing geographical coverages, time periods, definitions of urbanity and rurality, and adverse event outcomes should be acknowledged as potential sources of discrepancy.…”
Section: Discussionsupporting
confidence: 86%
“…It is thus clear that the present findings, obtained from a national dataset extending over a period of 10 years, are relevant for a broad population base. Unlike most previous studies ( Atmore et al, 2021 , Coburn et al, 2004 ), this study focused on deaths primarily attributed to adverse events, as they arguably constitute the most severe outcome in the patient safety context. Adverse event deaths were studied in relation to total inpatient deaths to account for trends in overall mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most RH doctors asserted that the patient safety in their RH was high, even possibly higher than in a base hospital. Studies in NZ and internationally have not found any association between rural location and increased risk of hospital harm, but patients in need of interhospital transfers were at increased risk,40 41 as would be expected with patients with emergency care-sensitive conditions.…”
Section: Discussionmentioning
confidence: 81%
“…1,11 A recent study showed that in hospitalised rural patients, the only harm difference between rural and urban hospitals occurred in patients who required inter-hospital transfer. 12 Although further information was not available, critically unwell patients may have contributed to this finding, raising important questions about the burden placed on rural hospital clinicians caring for very sick patients.…”
Section: Discussionmentioning
confidence: 99%